Differential regulation of tissue-resident and blood-derived macrophages in models of autoimmune and traumatic peripheral nerve injury - Sprenger-Svačina, Alina; Svačina, Martin K. R.; Gao, Tong; Ritzel, Rodney M.; McCullough, Louise D.; Sheikh, Kazim A.; Zhang, Gang (Frontiers in Immunology, 2024)
IntroductionThe current study focuses on understanding the functional role of different subsets of endoneurial macrophages in autoimmune polyneuropathies (AP) and traumatic peripheral nerve injury (TPNI), which holds potential for clinical application. Recent studies have advanced our understanding of the diverse origins of macrophages within peripheral nerves. However, there remains a gap in our knowledge regarding how endoneurial macrophages from different origins affect disease progression in AP versus TPNI.MethodsFlow cytometry was utilized to analyze macrophage phenotypes, including polarization states, cytokine production, and myelin phagocytosis in animal models of AP and TPNI. This study focuses on two distinct origins of macrophages, namely CD11b+F4/80hi tissue-resident (TRM) and CD11b+F4/80int blood-derived macrophages (BDM). The study utilized two animal models: the first was the spontaneous autoimmune peripheral polyneuropathy (SAPP) model in B7.2-null non-obese diabetic (NOD-B7.2-/-) mice, which serves as a model for inflammatory demyelinating polyneuropathy; the second model involved wild type C57BL/6 mice subjected to sciatic nerve crush injury, modeling TPNI. Behavioral, electrophysiological, and histological analyses were performed to assess peripheral nerve injury.ResultsThe study found that pro-inflammatory M1 macrophage polarization and tumor necrosis factor-alpha production by macrophages were more pronounced in the peripheral nerves of SAPP mice compared to those with TPNI, with the majority of these macrophages being TRM. In contrast, endoneurial macrophages in mice with TPNI were mainly BDM, exhibiting a less defined macrophage polarization and cytokine profile than TRM in AP mice. Interestingly, myelin phagocytosis was primarily driven by BDM in both SAPP and TPNI mice.DiscussionThis study offers novel insights into origin-dependent macrophage functions in AP and TPNI. Furthermore, these findings may help the future development of novel therapies targeting macrophage subsets of specific origin in AP and TPNI.